Branding strategy for the tourism attraction potential of Pura Pengelukatan Tirta Sudamala Wanagiri Buleleng - Deviana, Ni Komang; Misri, Misri; Putra, I Putu Aditya Prawira; Putra, Putu Gede Wirananda Manggala; Sapitri, Hawita (CV. Austronesia Akademika, 2024)
Tourism branding strategies are crucial for creating a unique and compelling identity for destinations to attract visitors. This study focuses on Pura Pengelukatan Tirta Sudamala, a spiritual temple located in Wanagiri Village, Bali, which holds significant potential as a religious and healing tourism destination. Despite its historical and cultural importance, the temple's potential remains underdeveloped and underexplored. The research objectives are to analyze the temple’s spiritual, cultural, and natural appeal and to propose an effective branding strategy to elevate its recognition as a healing tourism site. The study adopts a qualitative research methodology with a descriptive approach, utilizing in-depth interviews, field observations, and document analysis. Key stakeholders, including temple caretakers, local residents, and visitors, provided critical insights. Field observations highlighted the temple’s purification rituals rooted in Tri Kaya Parisudha and Panca Maha Bhuta concepts, combining spirituality, natural elements, and therapeutic experiences. The findings demonstrate that Pura Pengelukatan Tirta Sudamala possesses unique attributes for spiritual healing, including traditional purification practices, serene natural surroundings, and cultural heritage. However, challenges such as limited accessibility, inadequate promotion, and low visitor awareness hinder its development. To address these issues, the proposed branding strategy focuses on the 4A framework: Awareness, Attitude, Action, and Accessibility. Key strategies include increasing online visibility through social media, engaging with wellness tourism influencers, improving visitor facilities, and developing infrastructure. Collaborative efforts with travel agencies and local stakeholders are also recommended to enhance accessibility and sustainability.